In Vitro Antimicrobial Activity of Embelia Ribes Seeds - Vaibhav S Wagh; Vishal V Pande; Suyash T Raskar; Rushikesh R Shirsath; Sarthak S Dahale; Namrata D Kambale; Om S Waghmare (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: The commercially known as Baibidang, the fruits of the Embelia ribes plant are utilized to treat epilepsy, headaches, rhinitis, hemorrhage, and sleeplessness. Embelia ribes is beneficial for ringworm, intestinal worms, skin conditions, leprosy, itching, dental cavities, fever, headaches, and emaciation, among other conditions. Paste is used to treat skin infection. This plant contains several previously identified classes of components, like vilangin, christembine, quercitol, emblelina, and a volatile oil. Objectives: Embelin demonstrated antifertility, analgesic, anti-inflammatory, antioxidant, and anticancer properties in animal tests. As a consequence, Embelia is chosen as the subject of the current antibiotic investigation. The current study is to analyze the ethanol extracts of Embelia ribes seeds physicochemically and investigate their antibacterial properties. Materials and Methods: The antimicrobial activity against Staphylococcus aureus, Streptococcus faecalis, Streptococcus pyogenes, Escherichia coli, Salmonella typhi, Shigellaflexneri, Shigellaboydii, Shigellasonnei, Proteus mirabilis, Pseudomonas aeruginosa, Klebsiella pneumonia, and E. Results: Numerous bacterial and fungal pathogens that are assumed to be the cause of many common ailments were tested against the ethanolic extract. To evaluate the antibacterial activity of a plate, the zone where inhibition happens is assessed. The following boreholes were filled aseptically with standard solutions containing 500, 250, 125, 62.5, 31.25, and 15.625 mg/ml in 50 l, with ciproflaxin 10 g acting as a control sample. Conclusion: Embelin demonstrated significant antibacterial properties against Staphylococcus aureus, Streptococcus pyogenes, Shigellaflexneri, S. sonnei, and Pseudomonas aeruginosa, in addition to to most against Salmonella typhi, S. boydii, as well as Proteus mirabilis.